TERAPI BERMAIN PUZZLE DALAM MENINGKATKAN KETERAMPILAN SISWA DI SLB NEGERI GARUT KOTA - Sri Yekti Widadi; Wahyudin; Windi; Dika (Jurnal Pengabdian Masyarakat DEDIKASI, 2023)
Playing is a fun activity for children with special needs, by playing it can also support growth and development in children with special needs. The selection of games must adjust to the child's developmental abilities according to his age. This encourages children to explore and reduces the risk of frustration or tantrums while playing. The community service carried out aims to carry out play therapy activities in the form of puzzle play therapy by combining various shapes such as numbers, fruits, animals, and letters as an effort to improve the skills of children with special needs. This community service activity was carried out at the State Special School (SLB) Garut City. The target of this community service activity is Garut City SLBN students followed by grades 7 to 12 years. The methods and stages of implementing activities include preparation on January 9 and 10, 2023, the implementation stage on January 11, 2023, and the evaluation stage on January 12, 2023. Playing combination puzzles can improve the cognitive abilities of children with special needs. (SLB) Negeri Garut Kota Hari needs to make efforts to increase the knowledge of children with special needs through various scheduled and continuous play therapies, such as this combination puzzle game in order to improve children's skills.